Role of Interfaith Dialogue in Checking Religious Extremism - Huda, Fazrin (Philosophy and Progress, 2019)
The concept of interfaith dialogue is extremely significant in today‟s world. It is not a new concept. It has a historical and pragmatic significance. Religious extremism is a new threat to the world. Unfortunately, no one in this world is free from the threat of religious extremism and violence. This article adopts a qualitative approach and data are collected from both primary and secondary sources. This paper explores the role of interfaith dialogue to check religious extremism by taking interviews of seven respondents. It also argues that interfaith dialogue is very effective to check religious extremism along with the challenges of conducting an effective dialogue. These challenges may include the lack of proper knowledge of interfaith dialogue, prejudice of stereotypes religious ideas, misinterpretations and political misuse of religions, some common obstacles of conducting an interfaith dialogue. Last of all, the article also shows how the situation of Bangladesh can be improved through interfaith dialogue where there exists a combined effort from both common people and the government to check religious fanaticism and extremism. Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 93-108